Beyond agriculture versus nonagriculture: Decomposing sectoral growth–poverty linkages in five African countries - Dorosh, Paul A.; Thurlow, James (International Food Policy Research Institute, 2014)
The development debate in Africa south of the Sahara is often cast as “agriculture versus nonagriculture.” Yet this view overlooks the heterogeneity within these broad sectors and the synergies between them. We estimate sectoral poverty–growth elasticities using economywide models for five African countries. Our detailed treatment of nonagriculture complements an expanding literature disaggregating the growth–poverty relationship in agriculture. Although our estimated elasticities are higher for agriculture given the importance of farm incomes for the poor, the extent to which this is true varies by country. In fact, elasticities for certain nonagricultural sectors are much closer to those in agriculture. Overall, elasticities are typically higher for trade and transport services and manufacturing (agroprocessing).